Pointwise hemi-slant Riemannian submersions - Akyol, Mehmet Akif; Sayar, Cem (Ukrains’kyi Matematychnyi Zhurnal, 2023)
UDC 517.98 We introduce a new type of submersions, which is called pointwise hemi-slant Riemannian submersions, as a generalization of slant Riemannian submersions, hemi-slant submersions, and pointwise slant submersions from Kaehler manifolds onto Riemannian manifolds. We obtain some geometric interpretations of this kind of submersions with respect to the total manifold, the base manifold, and the fibers. Moreover, we present non-trivial illustrative examples in order to demonstrate the existence of submersions of this kind. Finally, we obtain some curvature equalities and inequalities with respect to a certain basis.